Learning Expectation, Perceived Organizational Support and Organizational Commitment among Students Majoring in Human Resource Management - Surinta, Pratanpound (Journal of Industrial Business Administration, 2024)
The aim of this research was to: (1) study the relationships between learning expectation and perceived organizational support and organizational commitment among students majoring in human resource management; and (2) study the predictability of learning expectation and perceived organizational support and organizational commitment among students majoring in human resource management. The sample size was 109 students majoring in human resource management. The research instruments consisted of a learning expectation questionnaire, a survey of organizational support, and an organizational commitment scale. The data were analyzed using Pearson’s product moment correlation coefficient and multiple regression. The results were as follows: 1. Learning expectations and perceived organizational support had a significantly positive relationship with organizational commitment (r =.436 and.443, respectively, p<.01). 2. Learning expectations and perceived organizational support could significantly predict turnover intention (p<.01). Both variables explained the 26.70 percent variance in turnover intention.